Public-private partnership as a business alliance for the implementation of social projects (Journal of Economic Research & Business Administration, 2022)
The reconstruction of areas recognized as socially important involves the integration of private capitalinto these sectors, and this is becoming a worldwide trend. Public-private partnership (PPP) opens awide range of opportunities in healthcare, such as the introduction of innovative methods of treatment,technical equipment of polyclinics, improving the quality of medical services, technical, methodologicalmodernization of laboratory centers in education. The importance of this problem for the economy ofthe country emphasizes the relevance of the study direction. The main purpose of the article is to provideways to accelerate the development of the social orientation of country`s infrastructure through themechanisms of public-private partnerships. In practice, the definition of the application of PPP mechanismsin general allows to determine that the digital Kazakh society becomes an important tool in itscreation. These issues actualize the need to create a partnership between the state and the private sectorand the application of solid experience on them. Theoretically, this article can serve as a basis for thedevelopment of a methodology for establishing a mutual partnership between the state and the privatesector. Statistical analysis, the method of aggregate (integral) capacity, and review and analytical methodswere used in the research.The methodology of public-private partnership developed according to its modern significance willallow to determine the rational use of possibilities of private sector in solution of actual problems ofnational economy, to improve the state organization of modes of people’s use of public goods, to modernize infrastructure, to accelerate construction of model of bilateral rationality and efficiency in optimalsolution of issues of economy diversification.Key words: public-private partnerships, social projects, public-business partnerships, risks.